Case Report: New phenotype of late-onset Stüve–Wiedemann syndrome due to a C-terminal variant in the LIFR gene - Melnik, Evgenia; Sharova, Margarita; Kenis, Vladimir; Morgul, Anna; Zabnenkova, Viktoria; Markova, Tatiana (Frontiers in Pediatrics, 2024)
Stuve-Wiedemann syndrome presents a challenge for early diagnosis due to its high neonatal lethality and potential autonomic dysfunction in children. Here we described a patient with a lateonset, arthrogryposis-like phenotype form of Stuve-Wiedemann syndrome. While most cases result in neonatal complications, our patient only showed camptodactyly, ulnar deviation of the whirst and minor facial features at birth, resembling an arthrogryposis-like phenotype. The condition went unnoticed until adolescence when noticeable gait and posture abnormalities emerged. Clinical and radiological findings confirmed the diagnosis of a benign Stuve-Wiedemann syndrome, with light autonomic dysregulation. Notably, our patient lacked typical bent bones features but showed widened metaphyses and thickened femoral necks. Genetic analysis revealed a novel variant in the last exon of the LIFR gene, possibly explaining the mild phenotype. This case expands our understanding of Stuve-Wiedemann syndrome variability, aiding in earlier detection and better medical-genetic counseling.